Distributed Backlog-Aware D2D Communication for Heterogeneous IIoT Applications - Farag, Hossam; Stefanovic, Cedomir; Gidlund, Mikael (2022)
Delay and Age-of-Information (AoI) are two crucial performance metrics for emerging time-sensitive applications in Industrial Internet of Things (IIoT). In order to achieve optimal performance, studying the inherent interplay between these two parameters in non-trivial task. In this work, we consider a Device-to-Device (D2D)-based heterogeneous IIoT network that supports two types of traffic flows, namely AoI-orientated. First, we introduce a distributed backlog-aware random access protocol that allows the AoI-orientated nodes to opportunistically access the channel based on the queue occupancy of the delay-oriented node. Then, we develop an analytical framework to evaluate the average delay and the average AoI, and formulate an optimization problem to minimize the AoI under a given delay constraint. Finally, we provide numerical results to demonstrate the impact of different network parameters on the performance in terms of the average delay and the average AoI. We also give the numerical solutions of the optimal parameters that minimize the AoI subject to a delay constraint.